2023
DOI: 10.1002/mnfr.202300156
|View full text |Cite
|
Sign up to set email alerts
|

The Bioactive Dietary Polyphenol Preparation Alleviates Depression and Anxiety‐Like Behaviors by Modulating the Regional Heterogeneity of Microglia Morphology

Abstract: ScopeThe goal of this study is to investigate the effects of a bioactive dietary polyphenol preparation (BDPP), which is made up of grape‐derived polyphenols, on microglial responses, as well as the underlying molecular mechanisms in depression and anxiety‐like behaviors.Methods and resultsThe study finds that treatment with BDPP significantly decreases depression‐like and anxiety‐like behaviors induced by chronic stress in mice, while leaving their locomotor activity unaffected. The study also finds that BDPP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In the case of CS, if selected foods could be used as a preventive measure to alleviate CS-related symptoms including depression, it would provide adolescents with safer health protection. Recent studies have revealed that some food-based active ingredients, such as polysaccharides, oligosaccharides, polyphenols and unsaturated fatty acids, have specific regulatory effects on some chronic stress-related health issues [ 13 , 14 , 15 , 16 , 17 ]. However, there is a lack of research on interventions for physiological and psychological function impairment in animals or humans experiencing CS during their growth period, which limits the development of products to improve CS.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of CS, if selected foods could be used as a preventive measure to alleviate CS-related symptoms including depression, it would provide adolescents with safer health protection. Recent studies have revealed that some food-based active ingredients, such as polysaccharides, oligosaccharides, polyphenols and unsaturated fatty acids, have specific regulatory effects on some chronic stress-related health issues [ 13 , 14 , 15 , 16 , 17 ]. However, there is a lack of research on interventions for physiological and psychological function impairment in animals or humans experiencing CS during their growth period, which limits the development of products to improve CS.…”
Section: Introductionmentioning
confidence: 99%